1965
DOI: 10.1001/archpedi.1965.02090030223025
|View full text |Cite
|
Sign up to set email alerts
|

Cat-Scratch Disease

Abstract: CAT-SCRATCH FEVER has become a newly recognized clinical entity, separable from other regional adenopathies by means of a specific skin test. This entity has also been termed nonbacterial regional lymphadenitis1 and, more recently, benign inoculation lymphoreticulosis.2 It was first reported in this country by Greer and Keefer 3 and since then, many hundreds of cases have been recorded (references 4-6 among others). These reports have outlined well the usual clinical course and some have even associated chroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1990
1990
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The recurrence of cat-scratch disease has rarely been reported. To the best of our knowledge, there are few case reports and a case series of CSD lymphadenitis recurrence in previously healthy patients [ 10 , 11 ]. CSD relapse in immunocompromised patients has been reported in a kidney recipient patient [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The recurrence of cat-scratch disease has rarely been reported. To the best of our knowledge, there are few case reports and a case series of CSD lymphadenitis recurrence in previously healthy patients [ 10 , 11 ]. CSD relapse in immunocompromised patients has been reported in a kidney recipient patient [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…The patient presented with suppurative inguinal lymphadenitis two years after the initial diagnosis and had no history of cat scratches or bites. The authors concluded that it probably resulted from a flare-up of the prior infection, but they did not rule out the possibility of reinfection [ 11 ].…”
Section: Discussionmentioning
confidence: 99%